1997
DOI: 10.1002/(sici)1097-4644(19971001)67:1<131::aid-jcb13>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Increases in mRNA levels of glucose transporters types 1 and 3 in Ehrlich ascites tumor cells during tumor development

Abstract: A common feature of many tumors is an increase in glucose catabolism during tumor growth. We studied the mechanism of this phenomenon by using Ehrlich ascites tumor bearing mice as the animal model. We found that Ehrlich ascites tumor cells possess only glucose transporter 1 (GLUT1) and GLUT3 but not GLUT2, GLUT4, or GLUT5. The mRNA levels of GLUT1 and GLUT3 increased progressively in the tumour during development; however, there were no changes observable in mRNA levels of glucose transporters of all types in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…It has been suggested that vanadate compounds activate GLUT4, an isoform of GLUT, in rat adipocytes and thereby improve insulin sensitivity by enhanced receptor binding (Dubyak & Kleinzeller 1980;Shechter & Karlish 1980;al-Attas et al 1995). Because the glucose transport mechanism of Ehrlich ascites tumour cells involves GLUT1 and GLUT3 (Au et al 1997) the purpose of this study was to determine whether vanadyl ion and its complexes also enhance glucose uptake in these cells. The time-course of 2-deoxyglucose transport into Ehrlich ascites tumour cells was measured by use of the tracer [ 3 H]2-deoxyglucose as the nonmetabolizable analogue.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that vanadate compounds activate GLUT4, an isoform of GLUT, in rat adipocytes and thereby improve insulin sensitivity by enhanced receptor binding (Dubyak & Kleinzeller 1980;Shechter & Karlish 1980;al-Attas et al 1995). Because the glucose transport mechanism of Ehrlich ascites tumour cells involves GLUT1 and GLUT3 (Au et al 1997) the purpose of this study was to determine whether vanadyl ion and its complexes also enhance glucose uptake in these cells. The time-course of 2-deoxyglucose transport into Ehrlich ascites tumour cells was measured by use of the tracer [ 3 H]2-deoxyglucose as the nonmetabolizable analogue.…”
Section: Resultsmentioning
confidence: 99%
“…Several observations indicate that a highly active glucose transport system is common to neoplastic and to transformed animal cells (Warburg 1956;Salter & Weber 1979). Ehrlich ascites tumour cells, which depend primarily on glycolysis for the provision of energy, have a highly ef®cient glucose transport system dependent upon glucose transporters (GLUT) GLUT1 and GLUT3 for the maintenance of growth (Crane et al 1957;Chan et al 1983;Au et al 1997). These cells can be easily propagated and used as an experimental system without the need for a complicated procedure to separate cells (Cuppoletti et al 1981), such as the free fatty acid-releasing assay, which might injure cellular membranes and also needs a number of rats (animals) for isolation of adipocytes (Nakai et al 1995).…”
mentioning
confidence: 99%
“…Previous studies reported that serum VEGF levels were positively correlated with the stage of ovarian cancer (19,20). Au et al (21) found that the mRNA levels of glucose transporter 1 and glucose transporter 3 of ascites tumor cells increased progressively in the tumor during development. Stewart et al (22) explored the relationship between glucose metabolism and growth of VX2 liver tumors using fluorine 18 fluorodeoxyglucose positron emission tomography/CT scan and found that the glucose utilization of tumors increased with tumor growth.…”
mentioning
confidence: 99%
“…Loss of GLUT3 expression is consistently observable at 4 days after ischemia, but is not observed 24 h after ischemia. Reduction and/or increment in GLUT1 mRNA and protein have been described in glial cell lines and astroglia of animal models (Au et al, 1997;Boado, 1998b;Bolz et al, 1996;Simpson et al, 1999). However, Kondo et al (2001) revealed decreases in GLUT1 immunoreactivity in several cortical areas and the hippocampus at later time points, e.g.…”
Section: Ischemiamentioning
confidence: 98%